Complicated spastic paraplegia in patients with AP5Z1 mutations (SPG48). (October 2016) - Hirst, Jennifer; Madeo, Marianna; Smets, Katrien; Edgar, James R.; Schols, Ludger; Li, Jun; Yarrow, Anna; Deconinck, Tine; Baets, Jonathan; Van Aken, Elisabeth; De Bleecker, Jan; Datiles, Manuel B.; et al.
Abstract : Objective: Biallelic mutations in the AP5Z1 gene encoding the AP-5 ζ subunit have been described in a small number of patients with hereditary spastic paraplegia (HSP) (SPG48); we sought to define genotype–phenotype correlations in patients with homozygous or compound heterozygous sequence variants predicted to be deleterious. Methods: We performed clinical, radiologic, and pathologic studies in 6 patients with biallelic mutations in AP5Z1 . Results: In 4 of the 6 patients, there was complete loss of AP-5 ζ protein. Clinical features encompassed not only prominent spastic paraparesis but also sensory and motor neuropathy, ataxia, dystonia, myoclonus, and parkinsonism. Skin fibroblasts from affected patients tested positive for periodic acid Schiff and autofluorescent storage material, while electron microscopic analysis demonstrated lamellar storage material consistent with abnormal storage of lysosomal material. Conclusions: Our findings expand the spectrum of AP5Z1 -associated neurodegenerative disorders and point to clinical and pathophysiologic overlap between autosomal recessive forms of HSP and lysosomal storage disorders.